Mitochondria-associated ER stress evokes immunogenic cell death through the ROS-PERK-eIF2α pathway under PTT/CDT combined therapy. (1st April 2023) - Feng, Xiaoli; Lin, Tian; Chen, Dong; Li, Zhiyang; Yang, Qiuping; Tian, Huiting; Xiao, Yao; Lin, Mingzhen; Liang, Min; Guo, Weihong; Zhao, Peng; Guo, Zhaoze
Abstract: Chemodynamic therapy (CDT) can effectively induce immunogenic cell death (ICD) in tumours and is thus a promising strategy for boosting the efficacy of immunotherapy. However, the mechanism by which CDT enhances ICD and lowers ICD efficiency is unknown and this restricts its clinical application. In this study, a second near-infrared (NIR-II) window irradiation-triggered hydrogen peroxide (H2 O2 ) self-supplying nanocomposite ((Cu2 Se-CaO2 )@LA) was constructed. The modified lauric acid was melted by the heat energy of the NIR-II irradiation, to expose the CaO2 nanoparticles, and they then reacted with water to produce H2 O2 and Ca 2+ . H2 O2 was then converted to hydroxyl radicals by the photothermal-enhanced CDT process of the Cu2 Se nanocubes. Notably, the CDT and Ca 2+ overload was found to induce sequential damage to the mitochondria and endoplasmic reticulum (ER), which upregulated the PERK-mediated eIF2α phosphorylation pathway and caused subsequent ICD. NIR-II irradiation of the (Cu2 Se-CaO2 )@LA also increased reactive oxygen species (ROS) formation and this was sufficient to increase dendritic cell maturation, attracting cytotoxic T lymphocytes, and suppressing tumour growth in vivo. Overall, we demonstrated that an enhanced CDT strategy under NIR-II exposure and H2 O2 self-supply can induce extensive ICD by inducing mitochondria-associated ER stress, which represents a highly effective and promising strategy for ICD amplification and tumour immunotherapy. Statement of significance: In this study, a second near-infrared window (NIR-II) irradiation-triggered and H2 O2 self-supplying nanocomposite (named (Cu2 Se-CaO2 )@LA) was constructed and tested both in vitro and in vivo . These nanoparticles demonstrated promising antitumor activity as designed. Mechanistically, the nanoparticles could damage mitochondria and upregulate the PERK-mediated eIF2αphosphorylation pathway, further causing endoplasmic reticulum stress, and inducing immunogenic cell death through dendritic cell maturation and cytotoxic T lymphocyte recruitment augmented activity. This system represents a highly effective and promising strategy for enhancing tumor immunotherapy and provides new insights for future studies and design refinements. Graphical abstract: Image, graphical abstract